A Sociolinguistic Study on Code Switching Used by Society in Baturaja Village - Wardhatun Nahdoh; Wiya Suktiningsih; Agus Syahid (Pioneer: Journal of Language and Literature, 2019)
This study discusses code switching used by society in Baturaja village. This study aims to determine the types of code switching used by Baturaja society and the factors that determine code switching. The theory used in this research is sociolinguistic theory about code switching, types of code switching, factor of code switching. This research is descriptive qualitative. The data collection instruments consist of observation, recording, transcribing data, interviews, and taking notes. Based on the analysis, it was found that there are two types of code switching used by Baturaja society. the first type is internal code switching, the transition of language from local languages to national languages or vice versa. The second type is external code switching, namely the transfer of languages from national languages to international languages or vice versa. There are several factors that affect code switching: a) speaker, b) listener or interlocutor, c) presence of a third person, d) change in situation, and e) change the topic.